Implications and Challenges in Implementing Halal Standard of Animal Feed and its Marketability - Hasim, Nur Asmadayana; Mohd Noor, Nurul Syazwani; Mhd Rodzi, Nur Anis Raihana; Hairulanuar, Nurhana Nazira; Mohd Kashim, Mohd Izhar Ariff (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
The increasing global demand for Halal animal products has spurred interest in Halal animal feed, driven by consumer preferences for ethically and religiously compliant goods. Despite its marketability, the implementation of Halal standards in animal feed faced significant challenges, as limited countries have an established Halal Standard for this sector. The objective of this article is to highlight the implications, and its challenges associated with Halal animal feed, along with assessing the potential Halal global economic marketability. This study employs a scoping review methodology, analyzing eight articles from 2016 to 2024, sourced from databases such as Scopus and Google Scholar to assess the current state of Halal animal feed standards and market dynamics. The review identified several key challenges, such as the difficulty of controlling impurities in feed ingredients, lack of comprehensive Halal integrity within the feed supply chain, and insufficient awareness and understanding of Halal principles among farmers. These issues complicate the certification process and create significant barriers to the widespread adoption of Halal animal feed standards. This paper filled a gap for the need of international cooperation in developing unified Halal standards for animal feed. It also proposes that increased education and awareness among stakeholders could potentially boost the integrity and credibility of the Halal supply chain. In conclusion, establishing an impressive Halal Standards and promoting education among farmers and industry players are essential towards impacting the growth and sustainability of this niche market.